Effect of an individualised high-protein, energy-restricted diet on anthropometric and cardio-metabolic parameters in overweight and obese Malaysian adults: a 6-month randomised controlled study. Issue 9 (5th April 2019) - Mitra, Soma Roy; Tan, Pui Yee
Abstract: The aim of this study was to investigate the effectiveness of the Hipcref (high-protein, energy-restricted, high-vitamin E and high-fibre) diet in Malaysian adults on body composition and metabolic parameters after an intervention period of 6 months. Overweight/obese Malaysian adults ( n 128; BMI≥23 kg/m 2 ) were randomised to the Hipcref ( n 65) or control diet ( n 63). The intervention group received Hipcref diet charts based on their personal preferences. The control group followed a generalised dietary advice based on Malaysian Dietary Guidelines, 2010. All participants were responsible for preparing their own meals. There was a significant treatment group×time effect on anthropometric parameters ( P <0·05) on an intention-to-treat basis. Pairwise comparisons revealed that Hipcref diet participants had significant reduction in weight, BMI, waist circumference, fat mass and percentage body fat at months 3 and 6 compared with baseline ( P <0·001). The control group had significant increase in weight and BMI at months 3 and 6 compared with baseline ( P <0·05). The Hipcref diet group had higher reduction in fasting insulin, insulin resistance and C-reactive protein levels compared with the control group at month 6 ( P <0·05). Post-intervention, compared with the control group, the Hipcref diet group was found to consume significantly higher percentage energy from protein, and PUFA, higher energy-adjusted vitamin E (mg) and fibre (g), and lower total energy, lower percentage energy from fat and carbohydrate ( P <0·05). The success of the Hipcref diet on overweight/obese Malaysian adults may be due to the combined effect of the nutrient composition of the Hipcref diet.